The Willow Pattern Plot stage 7 - Hunt, Rodrick (United Kingdom Oxford University Press, 2012)
The children are drawn into the world depicted on a blue-and-white willow pattern plate that Nadim bought as a gift for his mother. Inside this stylized realm, they encounter Kim Shee, a young girl forbidden by her father to leave her garden, and Chang, her love. The friends hatch a clever plan$1 (Busing a sash and distractions with lemons$1 (Bto help the pair escape. The key$1 (Bs magic sends the children back home after the adventure concludes.s
These books are part of the Oxford Reading Tree Level 7: Stories series, designed for children who are developing confidence and fluency in reading. The stories continue the popular adventures of Biff, Chip, Kipper, Wilf, and friends, combining everyday school life with imaginative journeys sparked by the magic key.